Regional studies and translation activities: experience in designing an interdisciplinary specialty of general higher education - Kalmakova, Alena G. (University Pedagogical Journal, 2025)
The issues of designing the geographical speciality of general higher education «regional studies and translation activities» are considered. The key feature of the new speciality is its interdisciplinary character which allows students to acquire a wide range of competences. The experience of designing an educational programme for this specialty is revealed. It is noted that the content of this educational programme will provide not only qualitative geographical and linguistic training of future specialists, but also flexibility of their professional competences, multiprofile, ability to multitask and intercultural communication.